The EIB Climate Survey 2020-2021 - The climate crisis in a COVID-19 world calls for a green recovery - European Investment Bank (European Investment Bank, 2021)
The third edition of the EIB Climate Survey shows that COVID-19 has changed people's perception of the climate emergency. Most Europeans now consider the pandemic to be the greatest challenge facing their countries, but climate change remains a crucial issue. Europeans say: the economic recovery from the crisis must address climate change governments should promote growth that emits less CO2 and makes societies more resilient to climate change modifying personal habits to address climate change is important technological innovation should be used to fix climate problems climate action and the transition to green economies must take into account social inequalities These findings are particularly important today because the climate and a green recovery are top priorities in the European Union and many other regions of the world. Read the latest survey to find out what people see as the most effective way to address the climate emergency, what people are willing to give up, what they expect from government policies, and how COVID-19 influences our views.